Boks : W.C.K.S. Gryf Toruń - K.K.S. Grom Gdynia. (Wejherowo : [s.n.], 1946)
Zawody miały miejsce w grudniu 1946 r. w Sali Domu Kolejarza w Gdyni.
Keywords: Boks -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Boks -- Polska -- Gdynia -- 1945-1970 -- plakaty